Efektivitas Metode Role Playing dan Role Model dalam Program Kampanye Sosial (Analisis Perbedaan Efektivitas Metode Role Playing dan Role Model dalam Program Kampanye Sosial âProduk Pangan Olahan Saguâ Kondur Petroleum S.A dalam Membentuk Keputusan Mengol - Pamekar, Galuh Gilang (Jurnal Ilmu Komunikasi, 2010)
Abstract : The objective of this research is to analyze the differences on the effectiveness of role playing and role model methods applied in social campaign program. Role playing and role model are the methods in social learning theoryâas a part of persuasion theoriesâwhich implicates to behavior change by affecting with modeling and participate of the target adopters. The social campaign âProduk Pangan Olahan Saguâ adopts these two methods to persuade target adopters to change their behavior as its campaign goal.